High-conductivity and high-strength aluminum alloy conductor material and preparation method thereof

By adding specific elements to aluminum alloy conductor materials and adopting specific preparation processes, the problem of insufficient conductivity and strength of existing aluminum alloy conductor materials is solved, and high conductivity and high strength aluminum alloy conductor materials are achieved to meet the high-efficiency transmission needs of modern power grids.

CN119889758APending Publication Date: 2025-04-25ELECTRIC POWER RES INST OF GUANGXI POWER GRID CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411806134.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The conductivity and strength of existing aluminum alloy conductor materials cannot meet the needs of modern power grids for efficient, safe and reliable power transmission.

Method used

By adding elements such as Zr, Ti, Mg, Mn, Ce, Fe, Si to the aluminum alloy conductor material, and using specific preparation processes, including smelting, cooling, solid solution, quenching, rolling, drawing and aging treatment, aluminium alloy conductor materials with high conductivity and high strength are generated.

Benefits of technology

The conductivity and tensile strength of aluminum alloy conductor materials have been significantly improved, with conductivity reaching 62% IACS and tensile strength greater than 150MPa, meeting the high-efficiency transmission needs of modern power grids.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889758A_ABST
    Figure CN119889758A_ABST
Patent Text Reader

Abstract

The invention discloses a high-conductivity and high-strength aluminum alloy conductor material and a preparation method thereof.The high-conductivity and high-strength aluminum alloy conductor material comprises Zr, Ti, Mg, Mn, Ce, Fe, Si and the balance Al; wherein the mass fraction of the Zr is 0.08%-0.12%, the mass fraction of the Ti is 0.1%-0.5%, the mass fraction of the Mg is 0.55%-1%, the mass fraction of the Mn is 0.1%-1%, the mass fraction of the Ce is 0.1%-0.5%, the mass fraction of the Fe is 0.1%-0.2%, the mass fraction of the Si is 0.5%, and the balance is Al. The conductivity of the aluminum alloy monofilament is improved to 62% IACS or above, and the tensile strength can reach 150 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrical conductor materials, and specifically relates to a high-conductivity and high-strength aluminum alloy conductor material and a preparation method thereof. Background Art

[0002] As the global demand for renewable energy continues to increase, power transmission and distribution systems are facing higher performance requirements. The limitations of traditional aluminum alloy conductor materials in terms of conductivity and strength can no longer meet the needs of modern power grids for efficient, safe and reliable power transmission. Therefore, the development of new high-strength and high-conductivity aluminum alloy conductor materials has become an important research direction in the field of electrical materials.

[0003] Aluminum alloys are widely used in the power transmission industry due to their excellent conductivity, light weight and corrosion resistance. At present, most of the conductor materials of wires and cables in my country are copper conductors. However, due to the shortage of copper resources in my country and the high price of copper, copper conductor materials account for about 70% of the cost of copper wires and cables, resulting in too high a cost for manufacturing copper wires and cables. However, the strength of pure aluminum does not meet the standard. Improving the conductivity and strength of aluminum alloy conductors is currently a difficult problem.

[0004] In order to solve these problems, existing patents usually improve the strength and conductivity of aluminum alloys by alloying and heat treatment. Patent No. CN 115612899 B discloses a method for preparing a Mg-Si-La-Cu-Mn aluminum alloy conductor material. In order to improve the conductivity of the aluminum alloy, an aging treatment part is added in the last part of its experiment. Its tensile strength is above 360Mpa, but since its experiment did not carry out rolling and drawing treatment, it is not of reference significance. Its conductivity is as low as 57.5% IACS, which fails to solve the problem of too low conductivity of aluminum alloy conductor materials; Patent No. CN 113921164B discloses a method for preparing a Si-Fe-Mg-B-Ni-Ce-La-Sc high-strength aluminum alloy cable. Its invention aims at the shortcomings of the prior art by adding Ni elements to increase the strength of aluminum alloy Category 5 conductors while maintaining the ductility and hardness of aluminum alloy conductors. Its tensile strength is greater than 150MPa, but its maximum conductivity is only 51% IACS. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide an aluminum alloy conductor material with high conductivity and high strength.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a high conductivity and high strength aluminum alloy conductor material, characterized in that it contains Zr, Ti, Mg, Mn, Ce, Fe, Si, and the rest is Al;

[0009] Wherein, in terms of mass fraction, the mass fraction of Zr is 0.08% to 0.12%, the mass fraction of Ti is 0.1% to 0.5%, the mass fraction of Mg is 0.55% to 1%, the mass fraction of Mn is 0.1% to 1%, the mass fraction of Ce is 0.1% to 0.5%, the mass fraction of Fe is 0.1% to 0.2%, the mass fraction of Si is 0.5%, and the rest is Al.

[0010] As a preferred embodiment of the high-conductivity and high-strength aluminum alloy conductor material of the present invention, the high-conductivity and high-strength aluminum alloy conductor material is calculated by mass fraction, wherein: the mass fraction of Zr is 0.12%, the mass fraction of Ti is 0.3%, the mass fraction of Mg is 0.75%, the mass fraction of Mn is 0.3%, the mass fraction of Ce is 0.3%, the mass fraction of Fe is 0.1%, the mass fraction of Si is 0.5%, and the rest is Al.

[0011] As a preferred solution of the high conductivity and high strength aluminum alloy conductor material of the present invention, it also has the following characteristics:

[0012] (i) Electrical conductivity greater than 62% IACS;

[0013] (ii) tensile strength greater than 150 MPa;

[0014] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a high-conductivity and high-strength aluminum alloy conductor material.

[0015] In order to solve the above technical problems, the present invention provides the following technical solution: the high conductivity and high strength aluminum alloy conductor material is obtained by batching, smelting, cooling, solid solution, quenching, rolling, drawing and aging according to mass percentage.

[0016] As a preferred embodiment of the preparation method of the present invention, the smelting temperature is 700-750°C.

[0017] As a preferred embodiment of the preparation method of the present invention, the solid solution condition is solid solution at 500°C for 1 hour.

[0018] As a preferred embodiment of the preparation method of the present invention, the quenching conditions are as follows: heating the aluminum alloy material to 500°C, rapidly cooling it in water, and aging it at 165°C for 6.5 hours.

[0019] As a preferred embodiment of the preparation method of the present invention, the rolling includes hot rolling and cold rolling, wherein the hot rolling conditions are rolling at 350°C with a rolling speed of 300 mm / s, and the cold rolling speed is 300 mm / s.

[0020] As a preferred embodiment of the preparation method of the present invention, the aging treatment temperature is 120° C. and the time is 8 hours.

[0021] Another object of the present invention is to overcome the deficiencies in the prior art and provide an aluminum alloy conductor material with high conductivity and high strength for use in aluminum alloy cables.

[0022] Beneficial effects of the present invention:

[0023] (1) The present invention achieves precipitation strengthening by compositely adding elements such as Mg, Mn, Ti, Zr, Si and Ce, combined with a specific preparation process. The process of converting the solid solution atoms into the precipitated phase effectively reduces the lattice distortion, thereby improving the electrical conductivity. In addition, the addition of magnesium and manganese helps to refine the grains, reduce the grain size, and improve the strength of the material. Through the synergistic effect of the above mechanisms, the comprehensive performance of the material is significantly improved. The electrical conductivity of the aluminum alloy single wire of the present invention is increased to more than 62% IACS, and the tensile strength can reach 150MPa.

[0024] (2) The functions and mechanisms of the alloying elements characterized by their amounts and compositions are as follows:

[0025] Zirconium Zr: Adding zirconium in appropriate amounts can significantly enhance the performance of aluminum alloys. This is mainly because the atomic radius of zirconium is slightly larger than that of aluminum. Zirconium diffuses in aluminum in a substitutional manner, and its diffusion activation energy is high, which can precipitate fine Al3Zr phases at the grain boundaries of subgrains. These phases are not easy to aggregate and grow, have high stability, and effectively prevent the occurrence of recrystallization. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0027] Figure 1 This is the SEM image of the sample in the deformation and aging state of the present invention.

[0028] Figure 2 The aluminum alloy wire entity is prepared from the high-conductivity and high-strength aluminum alloy conductor material of the present invention. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0032] Unless otherwise specified, all raw materials used in the examples of the present invention are commercially available, as shown in Table 1 for details.

[0033] Table 1

[0034] name Commercial channels Part Number High purity aluminum particles Northeast Nonferrous Metals 113007 Aluminum Silicon Alloy Northeast Nonferrous Metals 313141 Aluminum-magnesium alloy Northeast Nonferrous Metals 313121 Aluminum Zirconium Alloy Northeast Nonferrous Metals 313401 Aluminum Titanium Alloy Northeast Nonferrous Metals 313222 Aluminum-manganese alloy Northeast Nonferrous Metals 313251 Aluminum Cerium Alloy Northeast Nonferrous Metals 313399

[0035] Titanium Ti: The role of titanium is mainly reflected in grain refinement and strength improvement. Titanium can promote the grain refinement of aluminum alloys by forming fine titanium compounds as crystal nuclei, thereby enhancing the strength and toughness of the material. In addition, the compounds formed by titanium and aluminum precipitate during heat treatment, effectively hindering dislocation movement, further improving yield strength and tensile strength, and its good corrosion resistance can enhance the durability of the alloy in harsh environments. Although the conductivity of titanium is relatively low, adding an appropriate amount can optimize the microstructure of the alloy and indirectly improve the overall conductivity.

[0036] Cerium (Lanthanum) (Ce): Adding La, Ce or La-Ce mixed rare earth elements can effectively improve the microstructure and optimize the morphology of the eutectic structure. These rare earth elements react with aluminum, iron and silicon to form high-melting point compounds, which precipitate preferentially during the solidification process, providing a large number of heterogeneous nucleation points. In addition, the segregation of rare earth elements at the solid-liquid interface increases the fluctuation of the composition near the interface, thereby increasing the supercooling of the solid-liquid interface, promoting non-spontaneous nucleation, and achieving the effect of grain refinement. At the same time, the addition of cerium and lanthanum can also refine the coarse AlFeSi micron-sized particles in the cast structure and improve its morphology, thereby improving the electrical conductivity and ductility of the alloy.

[0037] Magnesium Mg: The role of magnesium is mainly reflected in solid solution strengthening and precipitation strengthening, which can effectively improve the strength of aluminum alloys. The addition of magnesium causes the aluminum lattice to distort, enhances the material's resistance to deformation, and precipitates compounds (such as Mg2Si) formed during heat treatment, further improving yield strength and tensile strength. In addition, magnesium also improves the corrosion resistance and ductility of aluminum alloys, making them easier to form during processing. At the same time, by optimizing the microstructure, it reduces the negative impact of impurity elements on electrical conductivity, thereby indirectly improving the overall electrical conductivity.

[0038] Manganese Mn: In the designed high-conductivity and high-strength aluminum alloy solution, manganese significantly improves the strength of the aluminum alloy through solid solution strengthening and precipitation strengthening. The dissolution of manganese causes the aluminum lattice to distort and enhances the ability to resist deformation. At the same time, the formed compounds (such as Al6Mn) precipitate during the heat treatment process, further improving the hardness of the alloy. In addition, manganese improves the corrosion resistance of the aluminum alloy, promotes grain refinement, and optimizes the microstructure, thereby improving the mechanical properties and electrical conductivity. It can also react with impurity elements to reduce their negative impact on the alloy properties, thereby improving the overall performance of the aluminum alloy.

[0039] Silicon Si: In the present invention, the characterized silicon and its content can react with aluminum, iron and rare earth elements to form a second phase, thereby reducing lattice distortion, which has a positive effect on the electrical conductivity and mechanical properties of the aluminum alloy conductor material.

[0040] Iron Fe: Iron, as a main component in industrial aluminum, has significant advantages. First, the addition of iron can improve the strength of aluminum alloys, especially during the casting process, where iron exists in the form of aluminum-iron-silicon compounds, which helps to improve the overall strength of the material. In addition, the presence of iron can also enhance the wear resistance of aluminum alloys, making them more durable during machining and use. At the same time, iron can promote the optimization of the crystal structure of aluminum alloys, improve the microstructure of the material, and thus improve its mechanical properties. At appropriate levels, the addition of iron can also improve the corrosion resistance of aluminum alloys, making their service life longer in harsh environments. It is worth noting that according to the research of the present invention, the addition of an appropriate amount of iron will not significantly reduce the conductivity of aluminum alloys, maintaining good electrical conductivity.

[0041] Example 1

[0042] This embodiment provides a method for preparing a high-conductivity and high-strength aluminum alloy conductor material:

[0043] Calculated by mass percentage, the steel comprises the following components: 0.08% Zr, 0.15% Ti, 0.15% Mn, 0.55% Mg, 0.15% Ce, 0.1% Fe, 0.5% Si, and the balance is Al.

[0044] (1) Melting: The prepared raw materials are melted in a vacuum induction melting furnace at 730°C to obtain molten aluminum alloy liquid, and the molten aluminum alloy liquid is protected by an inert gas argon (Ar) to prevent oxidation and maintain an inert atmosphere.

[0045] (2) Cooling: Pour the molten aluminum alloy liquid into a mold preheated to 200 degrees. After cooling in the mold, the aluminum alloy ingot should be cooled to room temperature (about 20-25°C) with a cross-section of 20×20mm for subsequent heat treatment.

[0046] (3) Heat treatment: The cooled aluminum alloy ingot is taken out and placed in a heating furnace, set at 500°C for solution treatment and kept warm for 1 hour. This process helps to promote the uniform distribution of alloy elements. Then, quenching treatment is carried out, the aluminum alloy material is heated to 500°C and quickly cooled in water, and aged at 165°C for 6.5 hours.

[0047] (4) Rolling: The aluminum alloy ingot after heat treatment and quenching is hot rolled, and the rolling temperature is set to 350°C. After multiple rolling passes, its cross section is gradually reduced. After hot rolling, cold rolling is performed at a rolling speed of 300 mm / s to further improve the strength and conductivity of the material. After 7 rolling passes, 9.5mm aluminum alloy round rod.

[0048] (5) Drawing: The aluminum alloy round rod is cold drawn by a wire drawing die and drawn 12 times to obtain Aluminum alloy monofilament.

[0049] (6) Aging: Aging treatment is carried out at 120°C, and then naturally cooled after keeping warm for 8 hours to improve ductility and reduce internal stress.

[0050] Example 2

[0051] This embodiment provides a method for preparing a high-conductivity and high-strength aluminum alloy conductor material:

[0052] Calculated by mass percentage, the steel comprises the following components: 0.1% Zr, 0.2% Ti, 0.2% Mn, 0.66% Mg, 0.2% Ce, 0.1% Fe, 0.5% Si, and the balance is Al.

[0053] (1) Melting: The prepared raw materials are melted in a vacuum induction melting furnace to obtain molten aluminum alloy liquid, and the molten aluminum alloy liquid is protected by an inert gas argon (Ar) to prevent oxidation and maintain an inert atmosphere.

[0054] (2) Cooling: Pour the molten aluminum alloy liquid into a mold preheated to 200 degrees. After cooling in the mold, the aluminum alloy ingot should be cooled to room temperature (about 20-25°C) with a cross-section of 20×20mm for subsequent heat treatment.

[0055] (3) Heat treatment: The cooled aluminum alloy ingot is taken out and placed in a heating furnace, set at 520°C for solution treatment and kept warm for 1 hour. This process helps to promote the uniform distribution of alloy elements. Then, quenching treatment is performed, the aluminum alloy ingot is heated to 500°C, quickly cooled in water, and aged at 165°C for 6.5 hours.

[0056] (4) Rolling: The aluminum alloy ingot after heat treatment and quenching is hot rolled, and the rolling temperature is set to 350°C. After multiple rolling passes, its cross section is gradually reduced. After hot rolling, cold rolling is performed at a rolling speed of 300 mm / s to further improve the strength and conductivity of the material. After 7 rolling passes, Aluminum alloy round rod.

[0057] (5) Drawing: The aluminum alloy round rod is cold drawn by a wire drawing die and drawn 14 times to obtain Aluminum alloy monofilament.

[0058] (6) Aging: Aging treatment is carried out at 120°C, and then naturally cooled after keeping warm for 8 hours to improve ductility and reduce internal stress.

[0059] Example 3

[0060] This embodiment provides a method for preparing a high-conductivity and high-strength aluminum alloy conductor material:

[0061] Calculated by mass percentage, the steel comprises the following components: 0.12% Zr, 0.3% Ti, 0.3% Mn, 0.75% Mg, 0.3% Ce, 0.1% Fe, 0.5% Si, and the balance is Al.

[0062] Melting: The prepared raw materials are melted in a vacuum induction melting furnace to obtain molten aluminum alloy liquid, and the molten aluminum alloy liquid is protected by an inert gas argon (Ar) to prevent oxidation and maintain an inert atmosphere.

[0063] (2) Cooling: Pour the molten aluminum alloy liquid into a mold preheated to 200 degrees. After cooling in the mold, the aluminum alloy ingot should be cooled to room temperature (about 20-25°C) with a cross-section of 20×20mm for subsequent heat treatment.

[0064] (3) Heat treatment: The cooled aluminum alloy ingot is taken out and placed in a heating furnace, set at 540°C for solution treatment and kept warm for 1 hour. This process helps to promote the uniform distribution of alloy elements. Then, quenching treatment is performed, the aluminum alloy ingot is heated to 500°C, quickly cooled in water, and aged at 165°C for 6.5 hours.

[0065] (4) Rolling: The aluminum alloy ingot after heat treatment and quenching is hot rolled, and the rolling temperature is set to 350°C. After multiple rolling passes, its cross section is gradually reduced. After hot rolling, cold rolling is performed at a rolling speed of 300 mm / s to further improve the strength and conductivity of the material. After 7 rolling passes, Aluminum alloy round rod.

[0066] (5) Drawing: The aluminum alloy round rod is cold drawn by a wire drawing die and drawn 14 times to obtain Aluminum alloy monofilament.

[0067] (6) Aging: Aging treatment is carried out at 120°C, and then naturally cooled after keeping warm for 8 hours to improve ductility and reduce internal stress.

[0068] Example 4

[0069] The aluminum alloy conductor materials prepared in Examples 1 to 3 and the comparative example were tested for conductivity and tensile strength. First, the conductivity test was performed. The experimental instrument was the QJ36S-2B DC low resistance tester of Shanghai Shuangte Electrical Instrument Co., Ltd. The aged aluminum alloy monofilament was straightened using a straightener. A 30 cm long test area was carved on the monofilament, and 12 points were extracted from it to calculate the average radius. The area was calculated and imported into the tester to obtain a resistivity. The conductivity of the wire was obtained by dividing 1.724 by the target resistivity using the international annealed copper % IACS standard. Then the tensile strength test was performed using a universal testing machine. The length of 30 cm was measured and the target wire was clamped into the fixture. The maximum breaking load was obtained by starting the universal testing machine. The tensile strength was obtained by dividing the maximum breaking load by the cross-sectional area of ​​the wire.

[0070] The results are shown in Table 2

[0071] Electrical conductivity (%IACS) Tensile strength(MPa) Example 1 62.1 158 Example 2 62.1 154 Example 3 62.4 151

[0072] Comparative Example 1

[0073] The difference from Example 3 is that, by mass percentage, the following components are included: 0.12% Zr, 0.3% Ti, 0.3% Mn, 0.75% Mg, 0.1% Fe, 0.5% Si, and the balance is Al. The rare earth elements are removed, and the remaining experimental steps are completely the same.

[0074] The electrical conductivity of the aluminum alloy conductor material obtained in this comparative example is 57.3% IACS, and the tensile strength is 126.7 MPa.

[0075] Comparative Example 2

[0076] The difference from Example 3 is that, by mass percentage, the following components are included: 0.12% Zr, 0.3% Ti, 0.3% Mn, 0.75% Mg, 0.3% Ce, 0.1% Fe, 0.5% Si, and the balance is Al. The aging treatment in step (6) is removed, and the other experimental steps are completely the same.

[0077] The electrical conductivity of the aluminum alloy conductor material obtained in this comparative example is 60.1% IACS, and the tensile strength is 122.7 MPa.

[0078] Comparative Example 3

[0079] The difference from Example 3 is that, by mass percentage, the following components are included: 0.12% Zr, 0.3% Ti, 0.3% Mn, 0.75% Mg, 0.3% Ce, 0.1% Fe, 0.5% Si, and the balance is Al. The hot rolling in step (4) is not performed but cold rolling is performed directly, and the other experimental steps are completely the same.

[0080] The aluminum alloy wire material obtained in this comparative example has a conductivity of 58.1% IACS and a tensile strength of 140.1 MPa.

[0081] Comparative Example 4

[0082] The difference from Example 3 is that, by mass percentage, the following components are included: 0.12% Zr, 0.3% Ti, 0.3% Mn, 0.75% Mg, 0.3% Ce, 0.1% Fe, 0.5% Si, and the balance is Al. The cold rolling in step (4) is not performed, but only hot rolling is performed, and the other experimental steps are completely the same.

[0083] The electrical conductivity of the aluminum alloy conductor material obtained in this comparative example is 60.4% IACS, and the tensile strength is 122.5 MPa.

[0084] Table 3

[0085] Electrical conductivity (%IACS) Tensile strength(MPa) Comparative Example 1 57.3 126.7 Comparative Example 2 60.1 122.7 Comparative Example 3 58.1 140.1 Comparative Example 4 60.4 122.5

[0086] Figure 1 This is the SEM image of the sample in the deformation and aging state of the present invention.

[0087] Figure 2 The aluminum alloy wire entity is prepared from the high-conductivity and high-strength aluminum alloy conductor material of the present invention.

[0088] The present invention adds Ce to the aluminum alloy melt, and a trace amount of Ce reduces the solid solubility of solute Si and Mg in the Al matrix, reduces the contribution of solid solution atoms Si and Mg to the resistivity of the alloy, and thus improves the conductivity of the aluminum alloy; the aging process of the present invention promotes the segregation of Mg and Si atoms to form Mg-Si clusters, and the precipitated phase is generally Mg2Si, which improves the conductivity. The quenching method and aging process affect the performance of Al-Mg-Si-Cu alloys. The maximum value of the tensile yield elongation of aluminum alloy materials is 6.5 hours at 160-170°C.

[0089] During the quenching process, the alloying elements of the aluminum alloy dissolve at high temperatures to form a solid solution. Aging treatment can cause these alloying elements to precipitate in the matrix to form fine strengthening phases; after quenching, there may be large internal stresses inside the aluminum alloy, and aging treatment can also help release these internal stresses, stabilize the microstructure of the material, and reduce the risk of deformation or cracking in subsequent use.

[0090] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A high conductivity and high strength aluminum alloy conductor material, characterized by: Contains Zr, Ti, Mg, Mn, Ce, Fe, Si, and the rest is Al; Wherein, in terms of mass fraction, the mass fraction of Zr is 0.08% to 0.12%, the mass fraction of Ti is 0.1% to 0.5%, the mass fraction of Mg is 0.55% to 1%, the mass fraction of Mn is 0.1% to 1%, the mass fraction of Ce is 0.1% to 0.5%, the mass fraction of Fe is 0.1% to 0.2%, the mass fraction of Si is 0.5%, and the rest is Al.

2. The high conductivity and high strength aluminum alloy conductor material according to claim 1, characterized in that: The high-conductivity and high-strength aluminum alloy conductor material is measured by mass fraction, wherein the mass fraction of Zr is 0.12%, the mass fraction of Ti is 0.3%, the mass fraction of Mg is 0.75%, the mass fraction of Mn is 0.3%, the mass fraction of Ce is 0.3%, the mass fraction of Fe is 0.1%, the mass fraction of Si is 0.5%, and the rest is Al.

3. The high conductivity and high strength aluminum alloy conductor material according to claim 1 or 2, characterized in that: It also has the following features: (i) Electrical conductivity greater than 62% IACS; (ii) Tensile strength greater than 150 MPa.

4. The method for preparing a high-conductivity and high-strength aluminum alloy conductor material according to claims 1 to 3, characterized in that: include, The high-conductivity and high-strength aluminum alloy conductor material is obtained by batching, smelting, cooling, solutionizing, quenching, rolling, drawing and aging according to the mass percentages as described in any one of claims 1 to 2.

5. The preparation method according to claim 4, characterized in that: The smelting temperature is 700-750°C.

6. The preparation method according to claim 4, characterized in that: The solutionizing condition is to carry out the solutionizing at 500° C. for 1 hour.

7. The preparation method according to claim 4, characterized in that: The quenching conditions are as follows: heating the aluminum alloy material to 500° C., rapidly cooling it in water, and aging it at 165° C. for 6.5 hours.

8. The preparation method according to claim 4, characterized in that: The rolling includes hot rolling and cold rolling, wherein the hot rolling condition is rolling at 350° C. and a rolling speed of 300 mm / s, and the cold rolling condition is rolling at a speed of 300 mm / s.

9. The preparation method according to claim 4, characterized in that: The aging treatment temperature is 120° C. and the time is 8 hours.

10. Use of the high conductivity and high strength aluminum alloy conductor material as claimed in claims 1 to 3 in aluminum alloy cables.

Citation Information

Patent Citations

  • High-strength aluminum alloy category 5 conductor for wind power torsion-resistant cable and preparation method thereof

    CN113921164B

  • A high-conductivity, fatigue-resistant aluminum alloy conductor material and its preparation method

    CN115612899B